Enhancing Students' Creativity in an Educational Digitization Environment: Improving the Diagnostic System of Capacity Modernization - Abdukodirov Akmalkhoja (Zien Journals, 2024)
The integration of digital technologies in educational settings has opened new avenues for fostering students' creativity. This scientific article explores the topic of improving the diagnostic system of capacity modernization to enhance students' creative abilities in an educational digitization environment. It delves into the significance of creativity in the context of 21st-century skills and discusses the challenges and opportunities associated with incorporating digital tools and platforms for creative development. The article proposes innovative approaches to diagnosing and nurturing students' creative capacities, highlighting the potential of technologyenabled assessments and personalized learning experiences. Moreover, it emphasizes the importance of teacher training, collaborative pedagogical practices, and supportive learning environments in maximizing students' creative potential. By improving the diagnostic system of capacity modernization, educators can empower students to thrive in a rapidly evolving digital landscape and become creative problem solvers and innovators
Keywords: creativity; educational digitization; diagnostic system